2022
DOI: 10.1038/s41420-022-01253-5
|View full text |Cite
|
Sign up to set email alerts
|

FHL1 mediates HOXA10 deacetylation via SIRT2 to enhance blastocyst-epithelial adhesion

Abstract: Recurrent implantation failure (RIF) is a rather thorny problem in the clinical practice of assisted reproductive technology. Due to the complex aetiology of RIF, its pathogenesis is far from fully understood, and there is no effective treatment available. Here, We explored the regulatory mechanism of the four half-domains of LIM domain 1 (FHL1), which is significantly downregulated in the endometrium of RIF patients, in blastocyst-epithelial adhesion. Indeed, FHL1 expression was dramatically increased in norm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Furthermore, in mice, KRT86 is upregulated in the uterus during implantation, which indicates that this keratin might be involved in embryo implantation [99]. Other proteins important for cell adhesion and embryo implantation were identified in ZI blastocysts: desmoplakin, plakophilin 1, annexin A2 and FHL1 [100,115,146,147].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in mice, KRT86 is upregulated in the uterus during implantation, which indicates that this keratin might be involved in embryo implantation [99]. Other proteins important for cell adhesion and embryo implantation were identified in ZI blastocysts: desmoplakin, plakophilin 1, annexin A2 and FHL1 [100,115,146,147].…”
Section: Discussionmentioning
confidence: 99%
“…FHL1, a member of the four-and-a-half-LIM-only protein family, might be involved in muscle development or hypertrophy. Another study showed that FHL1 promotes blastocyst-epithelial adhesion ( 31 ). Therefore, we speculated that FHL1 might mediate the excessive adhesion of endometrial epithelial cells to the ectopic milieu, which is the opposite role.…”
Section: Discussionmentioning
confidence: 99%